"The Most Belligerent Non-resistant": Lucretia Mott on Women's Rights. (October 2015) - Vetter, Lisa Pace
Lucretia Mott is widely recognized as a moral and spiritual leader in the abolitionist and early women's rights movements. She has been characterized as a disciple of William Lloyd Garrison, a proliferator of Mary Wollstonecraft's ideas, and a religious promoter of human rights whose efforts were surpassed by the theoretically sophisticated and politically astute Elizabeth Cady Stanton. These portrayals paradoxically elevate Mott's status while understating the originality of her views. This analysis examines Mott's speeches and writings in detail and finds that her unique theoretical contributions are shaped by a combination of elements: a radically anti-dogmatic worldview rooted in her progressive religious faith, an unwavering commitment to autonomy for all people, and an egalitarian conception of power. Careful study of Mott's work reveals a compelling alternative viewpoint in the early women's rights and abolitionist movements and provides important insight into the philosophical roots of contemporary feminism and pacifism.